Crystal growth technology - Byrappa, K.; Ohachi, T. (William Andrew Pub. ; Springer, 2003)
Crystals are the unacknowledged pillars of modern technology. The modern technological developments depend greatly on the availability of suitable single crystals, whether it is for lasers, semiconductors, magnetic devices, optical devices, superconductors, telecommunication, etc. In spite of great technological advancements in the recent years, we are still in the early stage with respect to the growth of several important crystals such as diamond, silicon carbide, PZT, gallium nitride, and so on. Unless the science of growing these crystals is understood precisely, it is impossible to grow them as large single crystals to be applied in modern industry. This book deals with almost all the modern crystal growth techniques that have been adopted, including appropriate case studies. Since there has been no other book published to cover the subject after the Handbook of Crystal Growth, Eds. DTJ Hurle, published during 1993-1995, this book will fill the existing gap for its readers. The book begins with "Growth Histories of Mineral Crystals" by the most senior expert in this field, Professor Ichiro Sunagawa. The next chapter reviews recent developments in the theory of crystal growth, which is equally important before moving on to actual techniques. After the first two fundamental chapters, the book covers other topics like the recent progress in quartz growth, diamond growth, silicon carbide single crystals, PZT crystals, nonlinear optical crystals, solid state laser crystals, gemstones, high melting oxides like lithium niobates, hydroxyapatite, GaAs by molecular beam epitaxy, superconducting crystals, morphology control, and more. For the first time, the crystal growth modeling has been discussed in detail with reference to PZT and SiC crystals.
Keywords: Crystal growth.; elektronické knihy; electronic books